Medical Mysteries and Conundrums: When Doctors May Not Help. Understanding Hashimoto’s Encephalopathy: A Guide for Patients, Families and Caregivers by Nicola Nelson, Susan Foley and Shari Lawler for the Hashimoto’s Encephalopathy SREAT Alliance - Bauer, Henry (Journal of Scientific Exploration, 2014)
Understanding Hashimoto’s Encephalopathy: A Guide for Patients, Families, and Caregivers by Nicola Nelson, Susan Foley, and Shari Lawler for the Hashimoto’s Encephalopathy SREAT Alliance. CreateSpace, 2013. 458 pp. $21.95 (paperback). ISBN 978-1484883099. Some number of people feel ill, yet mainstream medicine tells them via their doctors that there is no discernable reason for their symptoms and therefore no clear way to offer any real help. Sometimes the sufferers may be told that it’s psychological stress, “all in the head,” that there’s nothing “really” wrong even though the physical pains are indubitably felt; or perhaps that what they think they suffer from doesn’t even exist. Consider Chronic Lyme Disease, for example: The term ‘chronic Lyme disease’ is not recognized in the medical literature, and most medical authorities advise against long-term antibiotic treatment for ‘chronic Lyme disease’. Studies have shown that most patients diagnosed with ‘chronic Lyme disease’ either have no objective evidence of previous or current infection with B. burgdorferi or are patients that should be classified as having post-Lyme disease syndrome, which is defined as continuing or relapsing non-specific symptoms (such as fatigue, musculoskeletal pain, and cognitive complaints) in a patient previously treated for Lyme disease. (Wikipedia; Science-Based Medicine)